An Analysis of Noun Found in Song “Lonely” By Justin Bieber - Dhea Saragih (Journal Corner of Education, Linguistics, and Literature, 2023)
The aim of this research is to find out noun used in a song by Justin Bieber entitled “Lonely”. This research applied descriptive qualitative method. There are several steps researcher conducted, including read the song lyrics, discovered nouns from the lyrics, then classified nouns based on the types. Based on research analysis, researcher discovered 12 nouns with 5 types. Therefore, the research results showed that there are 12 common nouns, 7 for each concrete and countable nouns, and 5 for each abstract and uncountable nouns found in song entitled “Lonely”.